Spatiotemporal dynamics of HIV-1 transmission networks in a major migration hub: integrated phylogenetic and molecular evidence - Zhu, Min; Chen, Junfang; Sun, Zhou; Xu, Ke; Zhang, Xingliang; Wu, Sisheng; Ye, Ling; Xu, Xiaojuan; Luo, Wenjie (Frontiers in Microbiology, 2025)
ObjectiveHuman Immunodeficiency Virus type 1 (HIV-1) cross-regional transmission poses a critical challenge in China, particularly in high-mobility metropolitan centers. This study aimed to characterize the transmission dynamics between Hangzhou—a megacity with 11.9 million residents (42% migrants)—and other Chinese regions using molecular epidemiology.MethodsWe analyzed 4,249 Hangzhou-derived and 50,898 non-Hangzhou HIV-1 pol sequences. Molecular transmission network analysis was used to identify transmission clusters, and phylogenetic and Bayesian analyses were conducted to explore lineage characteristics, origins, and expansion of major clusters.ResultsMolecular transmission network analysis identified 3,317 clusters, incorporating 43.5% (1,848/4,249) of Hangzhou sequences and 32.4% (16,511/50,898) of non-Hangzhou sequences. Crucially, 276 mixed-origin clusters bridged regions, comprising 1,222 (28.8%) Hangzhou and 8,954 (17.6%) non-Hangzhou individuals. Cross-regional connectivity was dominated by Shenzhen (48.1% of 46,962 edges), followed by Beijing (16.5%) and Guangzhou (7.9%). Multivariable regression revealed significantly higher odds of cross-regional connection for males versus females (aOR = 1.376, CI: 1.011–1.869, p = 0.043), homosexual transmission (aOR = 1.28, CI: 1.057–1.550, p = 0.009), non-residents (aOR = 1.207, CI: 1.040–1.402, p = 0.014), and first CD4 + T-cell count of 200–500 cells/uL (aOR = 1.348, CI: 1.057–1.718, p = 0.016). For subtypes, CRF07_BC and URF (CRF07_BC/CRF01_AE) demonstrated significant cross-regional spread versus other subtypes (aOR = 0.163–0.508, p < 0.001). Phylogenetic analysis of all Hangzhou CRF07_BC sequences identified two distinct lineages. Within the largest transmission CRF07_BC cluster, 99.5% of cross-regionally linked Hangzhou sequences (558/561) belonged to Lineage 1 indicating lineage 1 driving cross-regional spread. Bayesian dating indicated major URF clusters (HZC1-3, NHZ) originated between 2014 and 2020 (evolutionary rate: 1.73 × 10−3 subs/site/year).ConclusionThese findings identify key transmission routes connecting Hangzhou to economically developed regions and highlight CRF07_BC/URF strains and mobility as critical drivers. Targeted interventions disrupting these high-risk pathways are urgently needed to reduce regional HIV spread.